Efficacy of maize inbred testers with varying levels of resistance to Striga for classifying Striga-resistant yellow-maize lines into heterotic groups - Zebire, D.; Menkir, A.; Adetimirin, Victor O.; Mengesha Abera, W.; Meseka, S.K.; Gedil, Melaku A (Informa UK Limited, 2022)
Identifying efficient testers for separating maize (Zea mays L.) inbred lines into heterotic groups can facilitate the development of superior hybrids. Striga-resistant yellow-maize inbred lines developed at the International Institute of Tropical Agriculture (IITA) do not have well established heterotic groups. This study was conducted to identify efficient testers for classifying yellow-maize inbred lines into heterotic groups. Thirty Striga-resistant inbred lines were crossed with three testers having varying levels of resistance to Striga. A trial comprising 90 testcrosses and two hybrid checks was conducted at two locations in Nigeria for 2 years under Striga-infested and non-infested conditions. The approach that involved specific combining ability (SCA) effects and mean grain yields was found to be more efficient than the heterotic group’s specific and general combining ability (HSGCA) grouping method in separating the 30 inbred lines into three heterotic groups. The tolerant and resistant testers were highly efficient in grouping the inbred lines into heterotic groups under Striga-infested and non-infested conditions using the two approaches. Striga-resistant yellow inbred lines assigned to two of the three major heterotic groups could be used as parents for developing superior hybrids and/or synthetics and for generating source populations for developing new maize inbred lines.